NO Reduction by Carbon Monoxide Over Cobalt on Zeolite Beta - Grisdanurak, Nurak; Nuntaitawegon, Benjamart; Kinger, Gerald (ASEAN Journal of Chemical Engineering, 2005)
This study focused on the selective catalytic reduction of nitric oxide (NO) by carbon monoxide (CO) over cobalt supported on zeolite beta (CoIBEA) with and without the presence of oxygen or water. The Co/BEA catalyst with 2.6% metal loading was prepared by solid state ion exchange from freshly synthesized HBEA and CoCl2’6H20. The adsorption behavior of NO on CoIBEA investigated by temperature programmed desorption (TPD) revealed two peaks for NO at 100 and 260°C indicating that there were at least two adsorption modes. The desorption of CO completed near 200°C along with a small amount of C02. The activity of ColBEA catalyst for NO reduction by CO was lower than 20% at 100-300°C but higher than 50% at 400-500°C with the maximum conversion of 60% at 500°C. Products were selectively N2 and C02. However, the activity in the presenceof oxygen was low due to the more favorable reaction between CO and 02 to form C02. The catalytic activity in the presence of water was also low but higher than that in the presence of oxygen.